MTOR modulation induces selective perturbations in histone methylation which influence the anti-proliferative effects of mTOR inhibitors - HaEun Kim; Benjamin Lebeau; David Papadopoli; Predrag Jovanovic; Mariana Russo; Daina Avizonis; Masahiro Morita; Farzaneh Afzali; Josie Ursini-Siegel; Lynne-Marie Postovit; Michael Witcher; Ivan Topisirovic (iScience, 2024)
Summary: Emerging data suggest a significant cross-talk between metabolic and epigenetic programs. However, the relationship between the mechanistic target of rapamycin (mTOR), which is a pivotal metabolic regulator, and epigenetic modifications remains poorly understood. Our results show that mTORC1 activation caused by the abrogation of its negative regulator tuberous sclerosis complex 2 (TSC2) coincides with increased levels of the histone modification H3K27me3 but not H3K4me3 or H3K9me3. This selective H3K27me3 induction was mediated via 4E-BP-dependent increase in EZH2 protein levels. Surprisingly, mTOR inhibition also selectively induced H3K27me3. This was independent of TSC2, and was paralleled by reduced EZH2 and increased EZH1 protein levels. Notably, the ability of mTOR inhibitors to induce H3K27me3 levels was positively correlated with their anti-proliferative effects. Collectively, our findings demonstrate that both activation and inhibition of mTOR selectively increase H3K27me3 by distinct mechanisms, whereby the induction of H3K27me3 may potentiate the anti-proliferative effects of mTOR inhibitors.